Improving Students’ Participation In English Learning Through Flashcards: A Classroom Action Research At Mi Nurul Mun’im - Nurfitriani Nurfitriani; Bradhiansyah Tri Suryanto; Siti Umniatul Khoiriyah (Journal of Innovative and Creativity, 2026)
Low student participation, with only 51% of 33 students actively involved, was a primary challenge in English learning for Class 3B at MI Nurul Mun'im. This Classroom Action Research (CAR) aimed to enhance student participation through the implementation of interactive flashcards. The study adopted the Kemmis and McTaggart model, conducted over two cycles, each comprising planning, acting, observing, and reflecting. Cycle I focused on using basic flashcards for guessing games and reading aloud activities with the theme "daily activities." Based on the reflection from Cycle I, Cycle II developed the use of flashcards by integrating games involving physical movement, such as "find your pair" and "flashcard race," with the theme " mealtimes, foods and drinks." Data were collected through student participation observation sheets, field notes, and photo/video documentation, then analyzed quantitatively and qualitatively. The results indicated a significant improvement in student participation. In Cycle I, participation increased to 75%. Following the implementation of Cycle II, student participation successfully reached 94%, exceeding the predetermined success indicator of 90%. The enhancement was evident not only in physical aspects (such as responding to questions and coming to the front of the class) but also in emotional (enthusiasm and confidence) and mental (focus and attention) aspects. This study concludes that flashcards, when used variably and contextually, are an effective medium for creating a dynamic learning environment, reducing student anxiety, and significantly boosting active participation in English learning at the elementary level. These findings recommend that teachers utilize flashcards in interactive learning activities to optimize students' basic learning processes.